(untitled) (Slavic Studies, 2024)
Starting from several theoretical premises for the term interpretation that are offered in literary hermeneutics, the purpose of our text is to illustrate those premises in a specific literary text. The analysis is focused on the novel Приглашение на казнь/ Invitation to a Beheading by Russian author Vladimir Nabokov.